2023
DOI: 10.3390/jmse11071288
|View full text |Cite
|
Sign up to set email alerts
|

Study on Mitigation of Wake Interference by Combined Control of Yaw Misalignment and Pitch

Abstract: Yaw misalignment can make a wake steer, which is an effective method to increase the power of wind farms but it also increases the fatigue load of the turbines. In this paper, the combination of yaw offset and pitch control (CYMP) is studied to analyse the potential mitigation of wake, focusing on the wind velocity and turbulence of the wake distribution, power increment, and fatigue load reduction. The simulation case study shows that the method of CYMP can reduce the fatigue load by 10.29% and increase the t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Fu et al [10] used a wind tunnel to collect wake data from floating offshore wind turbines and they discussed the influence of parameters like pitch and yaw oscillations on instantaneous power output and wake characteristics. Zhao et al [11] investigated the combination of wind turbine pitch and yaw control and found that the yaw load of the unit was reduced significantly under the combined effect of both, and the total power was increased by about 1.7%. Heisel et al [12] conducted wind tunnel experiments to study the meandering characteristics of wakes at the hub height of wind turbines.…”
Section: Introductionmentioning
confidence: 99%
“…Fu et al [10] used a wind tunnel to collect wake data from floating offshore wind turbines and they discussed the influence of parameters like pitch and yaw oscillations on instantaneous power output and wake characteristics. Zhao et al [11] investigated the combination of wind turbine pitch and yaw control and found that the yaw load of the unit was reduced significantly under the combined effect of both, and the total power was increased by about 1.7%. Heisel et al [12] conducted wind tunnel experiments to study the meandering characteristics of wakes at the hub height of wind turbines.…”
Section: Introductionmentioning
confidence: 99%
“…While individual turbine load control is typically achieved through independent pitch adjustments, frequent changes in pitch angles can result in increased fatigue loads on pitch bearings. To alleviate these additional fatigue loads, research is increasingly focused on wake control through wake redirection, aiming to reduce wake coverage [5,6], and providing a more comprehensive understanding of wind turbine load fluctuations.…”
Section: Introductionmentioning
confidence: 99%